Financial Frictions, Investment, and Institutions - Yafeh, Yishay; Claessens, Stijn; Ueda, Kenichi (Washington, D.C. : International Monetary Fund, 2010)
Financial frictions have been identified as key factors affecting economic fluctuations and growth. But, can institutional reforms reduce financial frictions? Based on a canonical investment model, we consider two potential channels: (i) financial transaction costs at the firm level; and (ii) required return at the country level. We empirically investigate the effects of institutions on these financial frictions using a panel of 75,000 firm-years across 48 countries for the period 1990 - 2007. We find that improved corporate governance (e.g., less informational problems) and enhanced contractual enforcement reduce financial frictions, while stronger creditor rights (e.g., lower collateral constraints) are less important.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet